A new species of the water mite genus Hygrobates Koch, 1837 (Acari: Hydrachnidia: Hygrobatidae) from the ancient Lake Ohrid - Pešić, Vladimir (Zootaxa, 2015)
A new water mite species, Hygrobates zawali n. sp., is described from material collected in the ancient Lake Ohrid on the Balkan Peninsula. This species has been confused for a long time with the rhithrobiontic H. diversiporus Sokolow, 1927, known from the Caucasus (Russia) and Turkey. The new species closely resembles H. quanaticola Schwoerbel & Sepasgozarian, 1976, a little documented species described from Iran, which is here illustrated based on re-examination of the type material. Furthermore, a key for the identification of species of the subgenus Rivobates Thor, 1897, from the Western Palaearctic is given.